2017
DOI: 10.1111/ene.13392
|View full text |Cite
|
Sign up to set email alerts
|

Chronic post‐stroke oropharyngeal dysphagia is associated with impaired cortical activation to pharyngeal sensory inputs

Abstract: Chronic post-stroke oropharyngeal dysphagia is associated with stroke severity and degree of leukoaraoisis. Impaired conduction and cortical integration of pharyngeal sensory inputs at stroke site are key features of chronic PSD. These findings highlight the role of sensory pathways in the pathophysiology of post-stroke oropharyngeal dysphagia and offer a potential target for future treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…Such a delay in time to LVC in PSOD associated with impaired safety of swallow was also observed in this study, almost doubling the time to LVC of healthy people, and was slightly above that previously described in comparable patients . Reduced pharyngeal sensitivity and impaired conduction and cortical integration of pharyngeal sensory inputs at the stroke site is a key feature of chronic PSOD and has been closely associated with impaired safety of swallow and delayed time to LVC . In fact, sensory feedback from the bolus is critical to tailor the motor component of the swallow response.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Such a delay in time to LVC in PSOD associated with impaired safety of swallow was also observed in this study, almost doubling the time to LVC of healthy people, and was slightly above that previously described in comparable patients . Reduced pharyngeal sensitivity and impaired conduction and cortical integration of pharyngeal sensory inputs at the stroke site is a key feature of chronic PSOD and has been closely associated with impaired safety of swallow and delayed time to LVC . In fact, sensory feedback from the bolus is critical to tailor the motor component of the swallow response.…”
Section: Discussionsupporting
confidence: 79%
“…While some patients recover spontaneously, 50% assessed 6 months poststroke were found to have chronic OD . The pathophysiology of PSOD is characterized by several motor impairments in the kinematics of the swallow response including delayed laryngeal vestibule closure (LVC) and decreased bolus propulsion forces ; also, patients affected by unilateral stroke showed a disrupted pattern of sensory cortical activation after pharyngeal stimulation as a distinctive marker of abnormal sensory integration of swallowing pathways in PSOD …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous independent study, we found that chronic poststroke OD was associated with stroke severity and the degree of leukoaraiosis present. In that study, we found that impaired conduction and cortical integration of pharyngeal sensory inputs at the stroke site were key features of poststroke OD, We also found that impaired safety of swallow in chronic poststroke patients was caused by specific impairments in the motor swallow response, including delayed timing of airway protection mechanisms and weak tongue propulsion forces …”
Section: Discussionmentioning
confidence: 88%
“…It has been demonstrated that the application of sensory stimulation in oropharyngeal area modulates swallowing performance and involves facilitation of swallowing initiation Sensory impairments in pharyngeal area are associated with penetration or aspiration in dysphagic patients, and oropharyngeal anesthesia results in disruption of swallowing movement even in healthy humans . Furthermore, impaired pharyngeal sensitivity is associated with reduced cortical activation …”
Section: Introductionmentioning
confidence: 99%